2016
DOI: 10.17235/reed.2016.4620/2016
|View full text |Cite
|
Sign up to set email alerts
|

What is the real-life maintenance mesalazine dose in ulcerative colitis?

Abstract: Objective: To describe how mesalazine (MSZ) is used in our practice in ulcerative colitis (UC), at what dose, and the success rate (regarding adherence to therapy).Methods: Observational, transversal study, including all patients with UC and with MSZ maintenance therapy seen from September 2014 to February 2015 at two IBD units in Spain. Treatment adherence was measured by the Morisky-Green scale.Results: We included 203 patients (mean MSZ dose: 2.6 ± 1.0 g/d; median of treatment: 19.5 months [IQR: 8-48]). Dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…This study found that there was no significant reduction in glomerular filtration rate while on either therapy . As it has been noted that nephrotoxicity with regard to mesalazine therapy has been documented to occur within 12 months of initiation of treatment, we recommend monitoring creatinine level at initiation of therapy, at 6 months, and again at 12 months.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…This study found that there was no significant reduction in glomerular filtration rate while on either therapy . As it has been noted that nephrotoxicity with regard to mesalazine therapy has been documented to occur within 12 months of initiation of treatment, we recommend monitoring creatinine level at initiation of therapy, at 6 months, and again at 12 months.…”
Section: Resultsmentioning
confidence: 76%
“…Incidence of erectile dysfunction while on mesalazine therapy has been noted to be 0.5% in one observational study . Furthermore, a retrospective study found that out of eight male patients with inflammatory bowel disease found to be infertile, seven were treated with mesalazine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It gives anti-inflammatory effects by increasing expression of peroxisome proliferator-activated receptors in gastrointestinal epithelial cells. Furthermore, it acts to inhibit COX enzymes, thus affecting prostaglandins and decreasing inflammation of the colon [12][13][14][15][16]. Unfortunately, it is difficult to cure UC completely, with 74% of patients experiencing at least one relapse during 5-year observation in a prospective population-based cohort study [17].…”
Section: Introductionmentioning
confidence: 99%
“…Mesalamine (MES) is currently the first-choice drug for UC, as it can be used to both cause and maintain the remission of UC (8)(9)(10). Meta-analyses indicated that the effective rate and remission rate of UC patients treated with MES was better than that in a placebo group (11,12). However, although only a small amount of MES reaches the…”
Section: Introductionmentioning
confidence: 99%